Preconditioning with Lipopolysaccharide or Lipoteichoic Acid Protects against Staphylococcus aureus Mammary Infection in Mice - Breyne, Koen; Steenbrugge, Jonas; Demeyere, Kristel; Vanden Berghe, Tom; Meyer, Evelyne (Frontiers in Immunology, 2017)
Staphylococcus aureus is one of the most causative agents of mastitis and is associated with chronic udder infections. The persistency of the pathogen is believed to be the result of an insufficient triggering of local inflammatory signalling. In the current study, the preclinical mastitis model was used, aiming to evaluate if lipopolysaccharide (LPS) or lipoteichoic acid (LTA) preconditioning could aid the host in more effectively clearing or at least limiting a subsequent S. aureus infection. A prototypic Gram-negative virulence factor, i.e. LPS and Gram-positive virulence factor, i.e. LTA were screened whether they were able to boost the local immune compartment. Compared to S. aureus-induced inflammation, both toxins had a remarkable high potency to efficiently induce two novel selected innate immunity biomarkers i.e. lipocalin 2 (LCN2) and chitinase 3-like 1 (CHI3L1). When combining mammary inoculation of LPS or LTA prior to a local S. aureus infection, we were able to modulate the innate immune response, reduce local bacterial loads and induce either LCN2 or CHI3L1 at 24 hours post-infection. Clodronate depletion of mammary macrophages also identified that macrophages contribute only to a limited extend to the LPS/LTA-induced immunomodulation upon S. aureus infection. Based on histological neutrophil influx evaluation, concomitant local cytokine profiles and LCN2/CHI3L1 patterns, the macrophage-independent signalling plays a major role in the LPS or LTA pretreated S. aureus-infected mouse mammary gland. Our results highlight the importance of a vigilant microenvironment during the innate immune response of the mammary gland and offers novel insights for new approaches concerning effective immunomodulation against a local bacterial infection.